Folate, Vitamin B12, and Homocysteine Levels in Women With Neural Tube Defect-Affected Pregnancy in Addis Ababa, Ethiopia - Kucha, Winner; Seifu, Daniel; Tirsit, Abenezer; Yigeremu, Mahlet; Abebe, Markos; Hailu, Dawit; Tsehay, Dareskedar; Genet, Solomon (Frontiers in Nutrition, 2022)
Background Neural tube defects (NTDs) are prevalent congenital defects associated with pre-pregnancy diet with low levels of maternal folate. They are linked to severe morbidity, disability, and mortality, as well as psychological and economic burdens. Objective The goal of this study was to determine the levels of folate, vitamin B12, and homocysteine in the blood of women who had a pregnancy impacted by NTDs. Subjects and Methods A hospital-based case–control study was undertaken between September 2019 and August 2020. The study comprised a total of 100 cases and 167 controls. Enzyme-linked immunosorbent assay (ELISA) was used to determine the levels of folate, vitamin B12, and homocysteine in the serum. Results Only 39% of the cases and 54.5% of control mothers reported periconceptional use of folic acid/multivitamin, which indicated a statistically significant difference (p = 0.014). Logistic regression indicated that periconceptional use of folic acid/multivitamin was associated with NTDs (p = 0.015, OR = 1.873, 95% CI: 1.131–3.101). We found that 57% of the cases and 33.5% of controls, as well as 43% of cases and 20.4% of controls had serum folate and vitamin B12 levels below the cut-off value, respectively. Twenty-seven percent of the cases and 6.6% of controls had hyperhomocysteinemia (HHcy). The median concentrations of folate, vitamin B12, and homocysteine in cases and controls were 4.78 and 8.86 ng/ml; 266.23 and 455 pg/ml; 13.43 and 9.7 μmol/l, respectively. The median concentration of folate (p < 0.001) and vitamin B12 (p < 0.001) were significantly lower in the cases than controls, while the homocysteine concentration (p < 0.001) was significantly lower in the controls than cases. Folate [OR (95% CI) = 1.652 (1.226–2.225; p = 0.001)], vitamin B12 [OR (95% CI) = 1.890 (1.393–2.565; p < 0.001], and homocysteine [OR (95% CI) = 0.191 (0.09–0.405; p < 0.001)] levels were associated with NTDs. Conclusion Folate and vitamin B12 are deficient in both cases and control mothers. The lower levels of folate and vitamin B12 with an elevated homocysteine level in NTD-affected pregnancy may be an indication that these biochemical variables were risk factors for NTDs. Folate/multivitamin supplementation and/or food fortification should be promoted.